PRESSURE-STATE-RESPONSE MODEL FOR ASSESSING ENVIRONMENTAL IMPACTS IN SERRA DO JAPI - Zignani Barroso de Lima, Luciana; dos Santos Batista, Marcelo; Rita Gritti Ferraretto, Tânia; Fávaro Augusto, Victor (Journal of Interdisciplinary Debates, 2023)
Serra do Japi, is located in the interior of the state of São Paulo, located in areas listed by CONDEPHAAT (Council for the Defense of Historical, Archaeological and Tourist Heritage of the State of São Paulo), being considered a remnant of the Atlantic Forest, covering the municipalities of Jundiaí, Cabreúva, Pirapora do Bom Jesus and Cajamar. The occupation of some areas and the development of human activities have changed their characteristics over the years.